ECG interpretation in Emergency Department residents: an update and e-learning as a resource to improve skills. (April 2017) - Barthelemy, Francois X.; Segard, Julien; Fradin, Philippe; Hourdin, Nicolas; Batard, Eric; Pottier, Pierre; Potel, Gilles; Montassier, Emmanuel
Abstract : Objective: ECG interpretation is a pivotal skill to acquire during residency, especially for Emergency Department (ED) residents. Previous studies reported that ECG interpretation competency among residents was rather low. However, the optimal resource to improve ECG interpretation skills remains unclear. The aim of our study was to compare two teaching modalities to improve the ECG interpretation skills of ED residents: e-learning and lecture-based courses. Participants and methods: The participants were first-year and second-year ED residents, assigned randomly to the two groups. The ED residents were evaluated by means of a precourse test at the beginning of the study and a postcourse test after the e-learning and lecture-based courses. These evaluations consisted of the interpretation of 10 different ECGs. Results: We included 39 ED residents from four different hospitals. The precourse test showed that the overall average score of ECG interpretation was 40%. Nineteen participants were then assigned to the e-learning course and 20 to the lecture-based course. Globally, there was a significant improvement in ECG interpretation skills (accuracy score=55%, P =0.0002). However, this difference was not significant between the two groups ( P =0.14). Conclusion: Our findings showed that the ECG interpretation was not optimal and that our e-learning program may be an effective tool for enhancing ECG interpretation skills among ED residents. A large European study should be carried out to evaluate ECG interpretation skills among ED residents before the implementation of ECG learning, including e-learning strategies, during ED residency. Abstract : Supplemental Digital Content is available in the text.